Pengembangan Media Aurbook (Augmented Reality Book) untuk Meningkatkan Hasil Belajar Siswa Kelas IV Pada Pembelajaran IPAS Materi Kearifan Lokal - Vina Indriana Rukmana; Novi Setyasto (Jurnal Penelitian Pendidikan IPA, 2025)
The purpose of this study was to develop and test the feasibility, effectiveness, and practicality of the Aurbook (Augmented Reality Book) media in order to improve student learning outcomes. This research is categorized as development research (R&D) using the Borg and Gall model. A total of 36 fourth-grade students of SDN Kalinegoro 3 in the 2024/2025 academic year were involved in this study, with a small-scale trial conducted on 12 class IVA students and a large-scale trial on 24 class IVB students. The validation results from media, material, and language experts show that the Aurbook media is declared "very feasible" with an average score of 83%, which reflects its feasibility. The level of satisfaction that is "very good" is shown by the results of the teacher and student response questionnaire, with a score of 100% from teachers and 87% from students, which illustrates the practicality of e-teaching materials. The effectiveness of the Aurbook media is proven by the results of the t-test which shows a significance value of 0.000 (< 0.05) and an N-gain of 0.69, which is included in the "moderate" category. The criteria for eligibility, practicality, and effectiveness to improve learning outcomes in science learning for grade IV at SDN Kalinegoro 3 on local wisdom material have been met by the Aurbook media.